2021
DOI: 10.3126/njdvl.v19i2.37686
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections in A Tertiary Hospital of Kathmandu: A Retrospective Study

Abstract: Introduction: Sexually transmitted infections (STIs) are the diseases that are transmitted by sexual contact if a partner is infected with agent known to cause infection of genitalia. This group of diseases pose a huge public health problem. This study aims to provide an insight on the prevalence of STIs in a tertiary care center dedicated to civil servants. Methods: This is a retrospective cross-sectional study. All patients diagnosed with STI in a dermatology out-patient of Civil Service Hospital, a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…This is in accordance with other studies from Nepal. 10,11 Similar results were seen in the studies from Pakistan. 14 Adolescents' employment status can be a risk factor for STDs as these young, enthusiastic generations will engage with more people in their jobs rather than in colleges and get higher chances of STIs, especially among females.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is in accordance with other studies from Nepal. 10,11 Similar results were seen in the studies from Pakistan. 14 Adolescents' employment status can be a risk factor for STDs as these young, enthusiastic generations will engage with more people in their jobs rather than in colleges and get higher chances of STIs, especially among females.…”
Section: Discussionsupporting
confidence: 86%
“…This is in concordance with other similar studies from Nepal. [9][10][11] Various studies from India also showed a similar male preponderance. 12,13 Females are predisposed to increase biological and social vulnerability to STIs, especially in a developing country like India.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…12 This finding is similar to a study done by Paudel et al, who found 8.9% cases of syphilis amongst all STIs. 13 While analyzing HIV status in patients with AGW, 2 (2.6%) were positive for HIV serology which is 18.6 times higher than the prevalence of HIV in the general population, which is 0.14%. 14 Amongst other coexistent STIs, syphilis was the most common in our study, which is similar to Mueller et al, and Barua et al 15,2 Hence, patients with AGW should be evaluated and, if required, tested for syphilis and HIV.…”
Section: Resultsmentioning
confidence: 96%